Monepantel is a non-competitive antagonist of nicotinic acetylcholine receptors from Ascaris suum and Oesophagostomum dentatum. Issue 1 (April 2018) - Abongwa, Melanie; Marjanovic, Djordje S.; Tipton, James G.; Zheng, Fudan; Martin, Richard J.; Trailovic, Sasa M.; Robertson, Alan P.
Abstract: Zolvix ® is a recently introduced anthelmintic drench containing monepantel as the active ingredient. Monepantel is a positive allosteric modulator of DEG-3/DES-2 type nicotinic acetylcholine receptors (nAChRs) in several nematode species. The drug has been reported to produce hypercontraction of Caenorhabditis elegans and Haemonchus contortus somatic muscle. We investigated the effects of monepantel on nAChRs from Ascaris suum and Oesophagostomum dentatum heterologously expressed in Xenopus laevis oocytes. Using two-electrode voltage-clamp electrophysiology, we studied the effects of monepantel on a nicotine preferring homomeric nAChR subtype from A. suum comprising of ACR-16; a pyrantel/tribendimidine preferring heteromeric subtype from O. dentatum comprising UNC-29, UNC-38 and UNC-63 subunits; and a levamisole preferring subtype ( O. dentatum ) comprising UNC-29, UNC-38, UNC-63 and ACR-8 subunits. For each subtype tested, monepantel applied in isolation produced no measurable currents thereby ruling out an agonist action. When monepantel was continuously applied, it reduced the amplitude of acetylcholine induced currents in a concentration-dependent manner. In all three subtypes, monepantel acted as a non-competitive antagonist on the expressed receptors. ACR-16 from A. suum was particularly sensitive to monepantel inhibition ( IC 50 values: 1.6 ± 3.1 nM and 0.2 ± 2.3 μM). We also investigated the effects of monepantel on muscle flaps isolated from adult A. suum . The drug did not significantly increase baseline tension when applied on its own. As with acetylcholine induced currents in the heterologously expressed receptors, contractions induced by acetylcholine were antagonized by monepantel. Further investigation revealed that the inhibition was a mixture of competitive and non-competitive antagonism. Our findings suggest that monepantel is active on multiple nAChR subtypes. Graphical abstract: Image 1 Highlights: Monepantel is a positive allosteric modulator of nematode DEG-3/DES-2 type nAChRs. We found monepantel inhibited acetylcholine induced contractions in Ascaris suum. Monepantel is a non-competitive antagonist of the Ascaris ACR-16 (nicotine preferring) nAChR. Monepantel inhibits O. dentatum levamisole & pyrantel sensitive nAChRs non-competitively. The mode of action of monepantel is complex and likely involves multiple targets.